Experiences of counselors participating in an innovative project to develop a training program for specialized foster parents of youth (13–18 years) - Israel, Pravin; Raae, Jan F.; Bjørnestad, Jone Ravndal (Frontiers in Psychology, 2023)
Background Children placed in foster care represent a vulnerable and distressed group that requires a high level of care. However, good training programs designed to address specific problems presented in specialized foster care are not easily accessible due to logistical, economic and structural barriers. The lack of easy access and a strong desire to provide high-quality services inspired counselors from a specialized foster care center on the frontline to initiate an innovative, developmentally relevant and locally grounded training program. Aims This study focuses on counselors’ experiences with the development of the training program and its impact on their work life. Method A qualitative research design within a participatory approach framework was used to understand the experiences of the counselors. All the counselors employed in the department and the leaders (n = 14) participated in the study. Data were gathered from participants, including the lead and second authors, using a semi-structured interview, and analyzed using thematic analysis. Results The analyses yielded three main categories: (i) Psychological Factors, (ii) Social Dynamics, and (iii) Leadership Style and Support. Each of the first two categories consisted of three subcategories. At the psychological level, the employees’ experiences reflected the psychological states and traits required to fuel the tasks required by the project. The social dynamics of working in a team influenced the work process and, in turn, were impacted by it. Lastly, leadership style and support provided the foundation for innovation to germinate and grow. Conclusion Engaging in a locally created training program was associated with a strong sense of collaboration and team spirit. Counselors reported high intrinsic motivation and a strong sense of personal pride and drive for their jobs. They were proactive in seeking colleagues with particular expertise and collaborated on project tasks despite differences. The leadership style reflected the presence of transformational leadership behaviors, signaling an organizational culture conducive to innovation. The study provides an example of how aligning employees’ personal aspirations with workplace goals and professional development can create a workplace in which employees feel it is enjoyable to go to work.